Addressing population health inequities: investing in the social determinants of health for children and families to advance child health equity. Issue 1 (18th February 2023) - Thornton, Rachel L.J.; Yang, Tracy J.
Abstract : Purpose of review: This review provides a critical assessment of recent pediatric population health research with a specific focus on child health equity. The review addresses: the role of the healthcare sector in addressing fundamental social drivers of health, challenges within healthcare organizations in addressing health-related social needs and the social determinants of health, and the rationale for incorporating race and racism in pediatric population health research and practice. Recent findings: The coronavirus disease 2019 pandemic brought greater attention to the disparities and inequities in American health and healthcare. In response to these stark inequities, many health systems are adopting efforts and initiatives to address social needs, social determinants of health, racism, and health equity. However, empirical evaluation detailing the effectiveness of these interventions and initiatives is limited. Summary: While attention to identifying social needs among pediatric populations is increasing, there is limited evidence regarding the effectiveness of these interventions in producing sustained reductions in health disparities. To advance child health equity, researchers should move beyond individual behavior modification and directly examine fundamental drivers of health inequities. These drivers include government and health policies as well as societal forces such as systemic racism.